Effects of a new running shoe design on the landing pattern and energy loss - Zhang, J.; McPhail, A.; An, W.; Naqvi, W.; Chan, D.; Au, I.; Luk, A.; Chen, T.; Cheung, R. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Minimalist running shoes have an increased popularity as it may simulate barefoot running (Altman and Davis, 2012; Pohl et al., 2008; Squadrone and Gallozzi, 2009) and reduce running economy (Cheung and Ngai, 2015). A newly designed minimalist with lug platform claims to promote running performance by simulating barefoot running mechanics and lowering the energy loss during impact. This study sought to compare the landing pattern, vertical loading rates, energy loss, and initial vertical body stiffness in a group of habitual shod runners who ran with this new footwear model. Methods: Fifteen habitual shod runners conducted two 10-minute treadmill running bouts with their usual running shoes and the minimalists with lug platform in a randomized order. Kinematics and kinetics data were collected from last 20 consecutive steps of each trial. Heel-strike ratio, vertical average (VALR) and instantaneous (VILR) loading rates, energy loss, and initial vertical body stiffness were compared between two shoe conditions using paired-t tests. Results: Runners demonstrated significant lower heelstrike ratio while running in minimalists with lug platform than usual shoes (Cohen`s d=0.62; p=0.032). However, only one out of 15 participants completely modified the landing pattern with the minimalists. VALR and VILR between two footwear conditions showed no significant difference (Cohen`s d=0.30-0.36; p=0.191-0.258). Initial vertical body stiffness (Cohen`s d=0.67; p=0.032) and energy loss (Cohen`s d=0.57; p=0.044) were found greater when running in minimalists with lug platform than in traditional running shoes. Discussions: Minimalists with lug platform promote non-heelstrike landing but not lead to lower vertical loading rates. Interestingly, the new shoe design does not enhance energy exchange. Instead, it leads to a greater energy loss than traditional running shoes, which could be explained by a higher initial vertical body stiffness. ABSTRACT FROM AUTHOR